Preparation method and application for growing single-walled carbon nanotube on silicon-based negative electrode material

By growing the SWNTs network on the surface of the silicon-based anode material, the problem of SWNTs aggregation in the silicon-based anode material is solved, the conductivity and structural stability of the material are improved, and the energy density and cyclic stability of the lithium-ion battery are significantly improved.

CN119764365AInactive Publication Date: 2025-04-04QINGDAO UNIV OF SCI & TECH

Patent Information

Application Number
CN202411713194.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The addition of single-walled carbon nanotubes (SWNTs) to the silicon-based negative electrode material is easy to aggregate into a bundle, making it difficult to obtain a uniformly distributed carbon tube network, affecting the material's conductivity and structural stability.

Method used

SWNTs network is grown on the surface of silicon-based negative electrode material by chemical vapor deposition technology, and silicon-based supported metal catalysts are prepared by impregnation combined with high-temperature calcination, and the catalyst and reaction parameters are optimized to achieve uniform growth of SWNTs.

Benefits of technology

By growing the SWNTs network on the surface of the silicon-based negative electrode material, the conductivity and structural stability of the material are significantly improved, the volume expansion during the charging and discharging process is suppressed, and the energy density and cycling stability of the lithium-ion battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005156265720000011
    Figure HDA0005156265720000011
  • Figure HDA0005156265720000012
    Figure HDA0005156265720000012
  • Figure HDA0005156265720000013
    Figure HDA0005156265720000013
Patent Text Reader

Abstract

The invention discloses a preparation method and application for growing a single-walled carbon nanotube on a silicon-based negative electrode material. The silicon-based supported metal catalyst with high metal dispersity, high activity and high stability is prepared by taking a silicon-based material with a high specific surface area as a carrier, taking a salt solution containing metal ions as a precursor, adopting a strategy of combining impregnation with high-temperature calcination and controlling the type of the carrier, the type of metal salt, the calcination temperature and the calcination time. A single-walled carbon nanotube is grown on a silicon-based supported metal catalyst by using a chemical vapor deposition technology, and a uniform single-walled carbon nanotube network is obtained on the surface of a silicon-based material by controlling carbon source components, gas flow, growth temperature and growth time, so that the conductivity of a silicon-based negative electrode is improved, and volume expansion in a charge-discharge process is inhibited; the silicon-based negative electrode material with high capacity and long service life is prepared, and the energy density of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials. Background Art

[0002] Lithium-ion batteries (LIBs) offer advantages such as high energy density, low self-discharge, no memory effect, a wide operating temperature range, and a long cycle life, offering promising market applications. Although LIB production processes are highly mature, the energy density of many mainstream products has long plateaued, making further breakthroughs difficult. Electrode materials, as core components, are crucial for determining energy density, making the development of high-capacity and long-life electrode materials a current research hotspot. Energy density can be increased by enhancing the lithium storage capacity of electrode materials, but due to the limitations of the lithium storage mechanism of positive electrode materials, significant capacity increases are difficult. In contrast, negative electrode materials offer greater potential for improvement in capacity and cycle life, and extensive research has been conducted on this topic. Therefore, with production processes approaching their limits and positive electrode material capacity improvements encountering bottlenecks, developing higher-performing negative electrode materials is crucial for achieving breakthroughs in the energy density of LIBs.

[0003] Currently, graphite anodes dominate the market, but their capacity is approaching its theoretical upper limit, meaning that LIBs using graphite anodes have difficulty achieving significant improvements in energy density. In contrast, silicon-based anodes have a theoretical capacity 10 times that of graphite. However, their lower conductivity and high volume expansion rate lead to poor cycling performance. Improving the conductivity and structural stability of silicon-based anodes is a current research focus. Conventional silicon-based anode structural design methods, such as core-shell, yolk-shell structures, and nanocarbon material networks, can improve mass transfer and stabilize the structure, but they also face the problems of complex preparation and high cost. In recent years, numerous studies have shown that adding carbon nanotubes to silicon-based anodes is one of the simplest and most effective strategies to improve their performance. Among them, single-walled carbon nanotubes (SWNTs) can form a conductive network even at extremely low addition levels and effectively mitigate the volume expansion effect through their strong adsorption between them and the silicon-based anode. At the same time, SWNTs and lithiated silicon undergo a "mechanical-chemical" interface coupling reaction to in situ reconstruct the three-dimensional network of the negative electrode, thereby enhancing the mechanical properties and electron and ion transport properties of the silicon-based negative electrode. SWNTs are generally added to the silicon-based negative electrode by mechanical stirring, but due to the strong adsorption force between the slender SWNTs tubes, SWNTs tend to aggregate into bundles, making it difficult to obtain a uniformly distributed carbon tube network. Therefore, achieving in situ growth of SWNTs on the surface of the silicon-based negative electrode and then preparing a uniformly distributed SWNTs network that is tightly bonded to the silicon-based negative electrode is the key to preparing high-performance and high-stability silicon-based negative electrodes.

[0004] The use of chemical vapor deposition technology to grow SWNTs on supported metal catalysts is a common method in industry and laboratories. Supported catalysts are mainly composed of high-specific-surface-area carriers and highly dispersed metal particles. The impregnation combined with high-temperature calcination method has the advantages of simple operation, high efficiency, rapidity, and a wide range of applications. It is a mature method for preparing supported catalysts. Therefore, using nano-silicon-based materials with high specific surface area as carriers, the silicon-based supported catalyst is prepared by impregnation combined with high-temperature calcination strategy. SWNTs are directly grown on the silicon-based material by chemical vapor deposition technology. Combined with the optimization of catalysts and reaction parameters, a uniform SWNTs network is prepared on the silicon-based negative electrode, improving the overall performance of the composite silicon-based negative electrode material, developing high-capacity and long-life silicon-based negative electrode materials, and improving the overall energy density of LIBs. Summary of the Invention

[0005] Purpose of the invention: This invention aims to break through the energy density bottleneck of lithium-ion batteries and develop silicon-based negative electrode materials with high capacity and long life. In order to solve the problem that SWNTs are easily aggregated into bundles when added to silicon-based negative electrode materials, a strategy of growing SWNTs on the surface of silicon-based negative electrode materials is proposed. Silicon-based supported metal catalysts are prepared by impregnation method combined with high-temperature calcination strategy. A uniform and strongly bonded SWNTs network is grown on the surface of the silicon-based negative electrode through chemical vapor deposition technology, thereby improving the conductivity of the silicon-based negative electrode and suppressing the volume expansion during charge and discharge, thereby improving the comprehensive performance of the silicon-based negative electrode material.

[0006] Technical solution: The preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials described in the present invention include the following steps:

[0007] (1) A silicon-based material with a high specific surface area is used as a carrier, a salt solution containing metal ions is used as a precursor, and the reaction conditions of impregnation combined with high-temperature calcination are regulated to prepare a silicon-based supported metal catalyst.

[0008] (2) Control the reaction parameters of chemical vapor deposition to directly grow a single-walled carbon nanotube network on the surface of a silicon-based material, and apply the obtained silicon-based negative electrode material to lithium-ion batteries.

[0009] Furthermore, in step (1), the silicon-based material with a high specific surface area is a powder material containing an active silicon component, including any one or more combinations of silicon, silicon monoxide, and silicon-carbon composite materials, with a particle size range of 10 to 100 nm.

[0010] Furthermore, in step (1), the salt solution containing metal ions is any one or more combinations of nitrates, chlorides, and acetylacetone complexes of transition metal ions.

[0011] Furthermore, in step (1), the reaction conditions of regulating the impregnation combined with high-temperature calcination include the type of carrier, the type of metal salt, the calcination temperature and the calcination time.

[0012] Furthermore, in step (1), the silicon-based supported metal catalyst is composed of a composite of silicon-based materials and transition metal nanoparticles.

[0013] Furthermore, in step (2), the reaction parameters for controlling chemical vapor deposition include carbon source components, gas flow rate, growth temperature and growth time.

[0014] Furthermore, in step (2), the silicon-based negative electrode material is composited with a silicon-based material and surface-grown single-walled carbon nanotubes.

[0015] Furthermore, in step (2), the lithium-ion batteries include button-type, soft-pack and square types.

[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: 1. The strategy of growing SWNTs on silicon-based materials can avoid the problem of agglomeration into bundles during the direct addition of SWNTs, and obtain a silicon-based negative electrode material coated with a uniform SWNTs network. 2. Using silicon-based powder materials as catalyst carriers has the advantages of low price, good thermal stability, and large specific surface area. 3. The preparation of silicon-based supported metal catalysts by impregnation combined with high-temperature calcination has the advantages of simple operation, high efficiency and speed, and a wide range of applications. 4. The chemical vapor deposition method has the advantages of low cost and strong controllability, and the SWNTs growth process is carried out under normal pressure conditions, with a short preparation time, which is conducive to the large-scale production and application of silicon-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the Raman spectrum of the samples grown at different temperatures in Example 1, with an excitation laser of 633 nm;

[0018] Figure 2 is the Raman spectrum of the samples grown at different temperatures in Example 1, with an excitation laser of 532 nm;

[0019] Figure 3 is an SEM image of the sample grown at 800°C in Example 1;

[0020] Figure 4 is a TEM image of the sample grown at 800°C in Example 1;

[0021] Figure 5 The electrochemical performance comparison between the silicon-based composite material grown at 800°C and the original silicon material in Example 1 is shown; DETAILED DESCRIPTION

[0022] In order to make the contents of the present invention more understandable, further explanation is provided below with reference to specific examples and drawings.

[0023] Example 1:

[0024] A preparation method and application of single-walled carbon nanotubes grown on a silicon negative electrode material, comprising the following steps:

[0025] (1) 0.17 g of RuCl3·3H2O was dissolved in deionized water to obtain a precursor solution. Then, 0.94 g of nano-silicon material was added to the precursor solution and stirred on a magnetic stirrer for 4 h. The impregnated sample was then placed in an oven at 100 °C for 24 h to completely dry it and ground into powder.

[0026] (2) Place the catalyst in a quartz boat, place the quartz boat in the middle of a dual-temperature zone slide-type chemical vapor deposition furnace, connect the experimental device as required, set the furnace temperature program to 20°C / min, introduce argon at a flow rate of 500 sccm to remove the air in the device, wait until the sample temperature reaches the preset temperature (600°C-900°C), introduce carbon monoxide carbon source gas at a flow rate of 300 sccm for 20 minutes, turn off the carbon monoxide gas after the reaction is completed, and introduce argon. At the same time, stop heating and naturally cool to room temperature. Turn off the argon and take out the sample. Figure 1 and Figure 2 The Raman spectra in the graph show that at growth temperatures of 700℃ and 800℃, the -1 The peaks of SWNTs radial breathing modes (RBMs) were observed in the range with a large G / D peak intensity ratio. Figure 3 The SEM images in the figure show that the surface of the sample grown at 800℃ is covered with a large number of SWNTs. Figure 4 The TEM images in Figure 3 also clearly show the presence of nanoscale SWNTs in the sample grown at 800°C.

[0027] (3) Grind the prepared sample, conductive agent, and carboxymethyl cellulose in a mass ratio of 8:1:1. After grinding evenly, add appropriate deionized water solvent and grind again to form a uniform slurry. Then take out the slurry and coat it on copper foil with a four-sided coater, and then put it into an oven at 80°C to dry for 12 hours. After the temperature drops to room temperature, use a manual slicer to cut it into 12mm diameter discs, weigh the mass, and compact it with an electric tablet press. The assembly of the half-cell mainly uses CR2032 button cells, and the button cells are used to study the electrochemical properties of the active material. The assembly of the half-cell is all carried out in a glove box with high-purity argon (the content of moisture and oxygen is below 0.1ppm). The assembly steps are as follows: Place the electrode material sheet in the center of the positive electrode shell and add an appropriate amount of electrolyte. The electrolyte is a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing 1M lithium hexafluorophosphate (LiPF6) (volume ratio of 1:1). Then, cover it with a battery separator. The separator is a polypropylene separator (Celgared 2500). An appropriate amount of electrolyte is added. Then, a 14mm diameter lithium metal sheet is placed on top. A stainless steel gasket, spring, and negative electrode shell are placed in this order. The packaging is completed using a packaging machine. After standing at room temperature for 24 hours, electrochemical performance testing is performed. Figure 5 At a current density of 0.2Ag -1 The cycle stability diagram after 200 cycles shows that compared with the original silicon powder negative electrode, the silicon-based negative electrode material grown at 800°C has a higher specific capacity and better cycle stability at this current density.

[0028] Example 2:

[0029] A preparation method and application of single-walled carbon nanotubes grown on silicon monoxide negative electrode material, comprising the following steps:

[0030] (1) 0.19 g of Co(NO3)2·6H2O was dissolved in deionized water to obtain a precursor solution. Then, 1.46 g of silicon dioxide material was added to the precursor solution and stirred on a magnetic stirrer for 4 h. The impregnated sample was then placed in an oven at 100 °C for 24 h to completely dry it and ground into powder.

[0031] (2) Place the catalyst in a quartz boat, and place the quartz boat in the middle of a dual-temperature zone slide-type chemical vapor deposition furnace. Connect the experimental device as required, set the furnace heating program to 20°C / min, and introduce argon at a flow rate of 500 sccm to remove the air in the device. After the sample temperature reaches 900°C, introduce methane gas at a flow rate of 300 sccm for 20 minutes. After the reaction is completed, turn off the methane gas and introduce argon. At the same time, stop heating and cool naturally to room temperature. Turn off the argon and take out the sample.

[0032] (3) Grind the prepared sample, conductive agent, and carboxymethyl cellulose in a mass ratio of 8:1:1. After grinding evenly, add appropriate deionized water solvent and grind again to form a uniform slurry. Then take out the slurry and coat it on copper foil with a four-sided coater, and then put it into an oven at 80°C to dry for 12 hours. After the temperature drops to room temperature, use a manual slicer to cut it into 12mm diameter discs, weigh the mass, and compact it with an electric tablet press. The assembly of the half-cell mainly uses CR2032 button cells, and the button cells are used to study the electrochemical properties of the active material. The assembly of the half-cell is all carried out in a glove box with high-purity argon (the content of moisture and oxygen is below 0.1ppm). The assembly steps are as follows: Place the electrode material sheet in the center of the positive electrode shell and add an appropriate amount of electrolyte. The electrolyte is a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing 1M lithium hexafluorophosphate (LiPF6) (volume ratio of 1:1). Then, cover it with a battery separator. The separator is a polypropylene separator (Celgared 2500). An appropriate amount of electrolyte is added. Then, a 14mm diameter lithium metal sheet is placed on top. A stainless steel gasket, spring, and negative electrode shell are placed in this order. The packaging is completed using a packaging machine. After standing at room temperature for 24 hours, electrochemical performance testing is performed.

Claims

1. A preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials, characterized in that: Using silicon-based materials with high specific surface area as carriers and salt solutions containing metal ions as precursors, the reaction conditions of impregnation combined with high-temperature calcination are regulated to prepare silicon-based supported metal catalysts. The reaction parameters of chemical vapor deposition are controlled to grow single-walled carbon nanotube networks on silicon-based materials. The obtained silicon-based composite materials are applied to lithium-ion batteries.

2. The preparation method and application of growing single-walled carbon nanotubes on silicon-based negative electrode materials according to claim 1, characterized in that: The silicon-based material with high specific surface area is a powder material containing active silicon components, including any one or more combinations of silicon, silicon monoxide, and silicon-carbon composite materials, and the particle size ranges from 10 to 100 nm.

3. The preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials according to claim 1, characterized in that: The salt solution containing metal ions is any one or more combinations of nitrates, chlorides and acetylacetone complexes of transition metal ions.

4. The preparation method and application of growing single-walled carbon nanotubes on silicon-based negative electrode materials according to claim 1, characterized in that: The reaction conditions of the regulated impregnation combined with high temperature calcination include carrier type, metal salt type, calcination temperature and calcination time.

5. The preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials according to claim 1, characterized in that: The silicon-based supported metal catalyst is composited from silicon-based materials and transition metal nanoparticles.

6. The preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials according to claim 1, characterized in that: The reaction parameters for controlling chemical vapor deposition include carbon source components, gas flow, growth temperature and growth time.

7. The preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials according to claim 1, characterized in that: The silicon-based composite material is composited from silicon-based materials and grown single-walled carbon nanotubes.

8. The preparation method and application of single-walled carbon nanotubes grown on silicon-based negative electrode materials according to claim 1, characterized in that: The lithium-ion batteries include button type, soft pack and square type.

Citation Information

Patent Citations

  • Method for preparing porous silicon carbon nanotube composite negative electrode material of lithium ion battery by diatomite

    CN105845911A

  • Silicon-based negative electrode material of lithium ion battery, preparation method of silicon-based negative electrode material, and battery

    CN110034282A

  • Method for in-situ growth of carbon nanotube from silicon or oxide thereof

    CN111799448A

  • Composite particle for electrode, its manufacturing method, and nonaqueous electrolyte secondary battery

    JP2006244984A

Cited By

  • Preparation method of sand field straw and carbon nanotube composite pressure sensor

    CN121762078A